2021
DOI: 10.1029/2020wr029472
|View full text |Cite
|
Sign up to set email alerts
|

Review of Data Science Trends and Issues in Porous Media Research With a Focus on Image‐Based Techniques

Abstract: Most of the nature-made structures from lifeless objects and particles to living beings that surround us are porous at some level in a closer look. That is a reason why porous material research is fundamentally beneficial for many engineering, scientific, and biomedical fields from geoscience, water resources

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 278 publications
(503 reference statements)
0
10
0
Order By: Relevance
“…Evaluating their efficacy on 3D images of rocks can critically improve digital rock physics workflows (e.g., to achieve large fields of view with high resolution or enhance fast 4D low quality scans). Although pioneering efforts have been made to apply these methods to digital rocks, they mainly focused on sedimentary rocks and employed LR images synthetically downsampled from HR images 20 , 25 . Janssens et al 18 recently showed that synthetically downsampled LR images are often able to retain microstructure complexities, largely compromised in real LR scans by imaging artefacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating their efficacy on 3D images of rocks can critically improve digital rock physics workflows (e.g., to achieve large fields of view with high resolution or enhance fast 4D low quality scans). Although pioneering efforts have been made to apply these methods to digital rocks, they mainly focused on sedimentary rocks and employed LR images synthetically downsampled from HR images 20 , 25 . Janssens et al 18 recently showed that synthetically downsampled LR images are often able to retain microstructure complexities, largely compromised in real LR scans by imaging artefacts.…”
Section: Resultsmentioning
confidence: 99%
“…Testing the effectiveness of these methods on digital rocks with different features can be thus critical to improve digital rock physics workflows, such as to achieve large sample volume with high resolution or enhance fast low quality scans (e.g., for samples to be preserved and 4D imaging with large experimental apparatus and/or high temporal resolution). Some pioneering efforts have been done in this direction, leading to very promising results, although in most cases LR images were synthetically downsampled from HR scans and only conventional sedimentary digital rocks were employed 18 , 20 25 (for details see 20 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated to compare and analyze the differences and correlations between 2D images and 3D volumes when calculating the same parameter. The specific details of 2D digital image analysis for pore/grain parameters are available in our previous publication (Rabbani et al., 2021). Our findings indicate a strong positive correlation between the average pore/throat size in 3D and the average pore/throat size in 2D (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…Combining well logging or key parameter data with 1D CNN models, the physical properties of rocks, such as permeability and mechanical properties, can be accurately estimated, thereby enhancing our understanding of subsurface formations (Hu & Zhang, 2023; Li et al., 2022; Li & Misra, 2018; Prifling et al., 2021; L. Wu et al., 2023). For predicting image‐based 3D properties, CNNs directly finds many reliable microstructure‐property correlations to rapidly estimate physical properties of porous rocks, such as permeability, porosity, SSA and tortuosity (Table 1) (Alqahtani et al., 2020; Da Wang et al., 2021; Kamrava et al., 2020; M. Liu et al., 2023; Rabbani et al., 2020, 2021; Tahmasebi et al., 2020). Compared with the numerical simulation on 3D volume, CNNs require relatively low computational cost (Cang et al., 2018; Karimpouli & Tahmasebi, 2019; H. Wei et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Barring the inefficiency, subjectivity, and lack of scalability of manual approaches, integrating qualitative/semi-quantitative descriptions into reservoir characterization schemes remains challenging, primarily due to the quantitative nature of the other input data modalities (e.g., well-logs, seismic lines, core plug petrophysical measurements, etc.) (Rabbani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%